X-Linked Adrenoleukodystrophy: Molecular and Functional Analysis of the ABCD1 Gene in Argentinean Patients - Amorosi, Cyntia Anabel (2012)
X-linked adrenoleukodystrophy (X-ALD) is an inherited disease associated with mutations in ABCD1 gene, located on Xq28. It is characterized by increased concentration of very long chain fatty acids (VLCFAs) in plasma and in adrenal, testicular and nervous tissues, due to a failure in peroxisomal -oxidation. Clinical heterogeneity varies from presymptomatic individuals to rapidly progressive cerebral ALD forms. A total of 44 individuals from 10 unrelated X-ALD Argentinean pedigrees were involved in this study. We examined the ABCD1 gene in 28 patients including carriers by sequencing of genomic PCR products. In 10 families there were 9 different mutations, eight of which were novel. The new changes found were verified by a combination of methods: bioinformatics programs and functional analysis. The spectrum of mutations consists of 3 frameshift, an insertion (p.Arg285fs*16), a deletion (p.Thr254Argfs*82) and a duplication (p.Glu380Argfs*21); a deletion (p.Ser572_Asp575del), a splicing mutation (c.1081+5G>C) and 3 novel single base pair substitution (p.Ala341Asp, p.His420Pro and p.Tyr547Cys). In one patient 2 changes were found: 1 known (c.2006A>G, p.His669Arg) and 1 new (c.55G>T, p.Ala19Ser). Expression studies of last change suggested that is a polymorphism because plasmid encoding ALDP with this change was effective in the restoration of defective -oxidation in X-ALD fibroblasts. But without sufficient evidence for c.55G>T (p.Ala19Ser), therefore we call variation change. In total four polymorphisms were found by the sequencing of the ABCD1 gene from our patients: two novel intronic IVS6+14T>A, IVS9-32C>T both frequent in our patients and two known, c.1548G>A (p.Leu516Leu) in exon 6 and c.2019C>T (p.Phe673Phe) in exon 10.